Mendesain Model Pembelajaran Sejarah Kebudayaan Islam Berbasis Multikultural di Perguruan Tinggi - Masruri, M. Hadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This article seeks to offer a learning design of multicultural on History of Islamic Culture in Higher Education. These multicultural values include an attitude of self-respect, an attitude of respect for others, an attitude of respect for the environment and cultural nature, an attitude of appreciating beauty, an attitude of appreciating beauty, and an attitude of appreciating wholeness. The six values of multiculturalism are expected to be internalized in learning by lecturers of Islamic Cultural History courses in Higher Education in a design of learning models, starting from planning to arrange curriculum, syllabus and semester course plans (RPS) or lecture event units (SAP), to arranging lecture material for History of Islamic Culture and its studen book. While the application of learning design includes strategy, methods and evaluation. However, this matter, at the level of its application in higher education as mentioned above will be meaningless, unless the SKI lecturer who is responsible for internalizing multicultural values as mentioned above has a high awareness of the values of multiculturalism. Without the SKI lecturers who are aware of multicuralism, the values of multiculturalism will never be internalized in the attitudes and personalities of students as well students.Â